2007
DOI: 10.1099/jmm.0.47031-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of biofilms produced by quorum-sensing-deficient clinical isolates of Pseudomonas aeruginosa

Abstract: The quorum-sensing (QS) systems control several virulence attributes of Pseudomonas aeruginosa. Five QS-deficient P. aeruginosa clinical isolates (CI) that were obtained from wound (CI-1), tracheal (CI-2, CI-3, CI-4) and urinary tract (CI-5) infections had previously been characterized. In this study, a flow-through continuous-culture system was utilized to examine in detail the biofilms formed by these isolates in comparison with the P. aeruginosa prototrophic strain PAO1. Analysis of the biofilms by confocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 43 publications
3
29
0
Order By: Relevance
“…The severity of P. aeruginosa infections is due to the production of different extracellular and cellassociated virulence factors including pyocyanin, flagella, and pili [2,3,4]. Another factor contributing to the pathogenesis of P. aeruginosa is its tendency to form organized communities, known as biofilms, when it attaches to biotic and abiotic surfaces [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of P. aeruginosa infections is due to the production of different extracellular and cellassociated virulence factors including pyocyanin, flagella, and pili [2,3,4]. Another factor contributing to the pathogenesis of P. aeruginosa is its tendency to form organized communities, known as biofilms, when it attaches to biotic and abiotic surfaces [1].…”
Section: Introductionmentioning
confidence: 99%
“…The biofilms of P. aeruginosa may also be formed on medical devices such as urinary catheters. In these settings, the antibiotic resistance engendered by biofilms presents a serious challenge to the treatment of chronic P. aeruginosa infections [2] Another virulence factor produced by P. aeruginosa is the blue redox-active exoproduct pyocyanin, the predominant phenazine pigment produced by this organism that can easily penetrate biological membranes. It is readily recovered in large quantities from cystic fibrosis patients infected by P. aeruginosa and from ear secretions of P. aeruginosamediated chronic otitis media.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have linked quorum sensing (QS), cell density control of gene expression involving acylhomoserine lactones (acyl-HSLs) (36, 69), and biofilm formation/development in P. aeruginosa (17,26,38,64), although some studies indicate that QS has little or no role, with QS mutants being proficient in biofilm formation (27,62,67,68). These discrepancies are generally linked to differences in biofilm model and/or culture conditions, and indeed, a recent study confirmed that the QS dependence of biofilm formation is nutritionally conditional (i.e., QS systems are needed for biofilm formation in some growth media [e.g., succinate] but not others [e.g., glucose or glutamate]) (73).…”
mentioning
confidence: 99%
“…Details of in vivo P. aeruginosa biofilm formation, structure, and properties are limited, with most of our understanding of these structures coming from the study of model biofilms formed in vitro (3,15,29,30,56,80,81,84). In vitro biofilm development in P. aeruginosa is characterized by bacterial surface attachment, followed by microcolony formation by clonal expansion or motility-driven cell-to-cell aggregation and subsequent formation of a flat, uniform, confluent biofilm or heterogeneous, structured biofilms characterized by cell aggregates or "mushroom" structures separated by channels or spaces (38,40).A number of studies have linked quorum sensing (QS), cell density control of gene expression involving acylhomoserine lactones (acyl-HSLs) (36, 69), and biofilm formation/development in P. aeruginosa (17,26,38,64), although some studies indicate that QS has little or no role, with QS mutants being proficient in biofilm formation (27,62,67,68). These discrepancies are generally linked to differences in biofilm model and/or culture conditions, and indeed, a recent study confirmed that the QS dependence of biofilm formation is nutritionally conditional (i.e., QS systems are needed for biofilm formation in some growth media [e.g., succinate] but not others [e.g., glucose or glutamate]) (73).…”
mentioning
confidence: 99%
“…Development of S. aureus biofilm on 1-cm catheter segments was achieved using a multicell flowthrough continuous-culture system (5,31). Catheter segments were secured in the flow cell with stainless steel brackets, the flow cells were attached to silicone tubing, and these units were sterilized by autoclaving.…”
Section: Methodsmentioning
confidence: 99%